Effect of preoperative oral isomaltulose on insulin resistance and glycemic variability in patients with type 2 diabetes mellitus: a randomized controlled trial - Wang, Chenyang; Shang, Yue; Wang, Jiameng; Sun, Li; Li, Zhengmin; Gao, Changjun (Frontiers in Nutrition, 2026)
Background/objectivesPreoperative oral carbohydrate alleviates postoperative insulin resistance and enhances recovery. Its utility in type 2 diabetes mellitus (T2DM) is debated due to hyperglycemia risks. Isomaltulose, a low-glycemic-index carbohydrate, has been shown to effectively attenuate postprandial glucose fluctuations and reduce metabolic stress on pancreatic β-cells in T2DM patients. This study investigated the effects of preoperative oral isomaltulose in patients with T2DM undergoing elective laparoscopic non-gastrointestinal surgery.Methods60 T2DM patients were randomized to receive either 300 mL of a solution containing 50 g isomaltulose (isomaltulose group) or plain water (Control group) 2–3 h preoperatively. The primary outcome was insulin resistance, assessed by the homeostasis model assessment (HOMA-IR) at 24 h post surgery. Secondary outcomes included perioperative glycemic variability, serum insulin levels, Perlas grade (assessed by pre-anesthesia gastric ultrasound), incidence of regurgitation and aspiration, perioperative subjective comfort scores, postoperative nausea and vomiting incidence (PONV), time of first flatus after surgery, surgical wound complications, length of postoperative hospital stay.ResultsBaseline characteristics were comparable. At 24 h postoperatively, the Isomaltulose group exhibited significantly lower HOMA-IR [6.89 ± 3.38 vs. 11.60 ± 4.34; mean difference = 4.71, 95% CI (2.70, 6.72), p < 0.001] and serum insulin levels [15.59 ± 5.58 vs. 24.54 ± 5.92 mU/L; mean difference = 8.94, 95% CI (5.97, 11.92), p < 0.001]. Although overall blood glucose was higher [155.70 (129.60–183.60) vs. 144.0 (113.40–182.25) mg/dL, p = 0.045], glycemic variability was significantly better [20.54% (16.19–26.69) vs. 27.95% (22.89–31.78), p < 0.001]. Gastric emptying (p = 0.24), patient comfort, PONV, and gastrointestinal recovery were similar. No regurgitation, aspiration, or serious complications occurred.ConclusionIn well-controlled T2DM patients, preoperative oral isomaltulose was associated with lower postoperative insulin resistance and reduced glycemic variability, without delaying gastric emptying. These metabolic benefits were accompanied by a transient elevation in pre-induction blood glucose, which should be weighed in clinical decision making.Clinical trial registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2500098088.